2013
DOI: 10.4081/ijas.2013.e87
|View full text |Cite
|
Sign up to set email alerts
|

Association betweenGPX5Gene Polymorphism and Selenium Concentration in Liver and Kidney of Wild Boars from West Pomerania Province, Poland

Abstract: The aim of the experiment was to detect polymorphism in the GPX5 gene and to determine associations between individual genotypes and selenium concentration in liver and kidney of wild boars from West Pomerania province in Poland. The polymorphism in GPX5 gene was detected using the PCR-RFLP method with specific primers and the restriction enzyme HinfI. Two different alleles of the GPX5 gene were identified -allele 1B (0.37) and 2B (0.63). The relationships between the GPX5 genotypes and concentrations of selen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(5 citation statements)
references
References 11 publications
3
2
0
Order By: Relevance
“…The genotypic frequencies of AA, AG and GG were 0.157, 0.478 and 0.365 and allelic frequencies of A and G were 0.396 and 0.604, respectively, in the studied breed. The frequency of 1B2B (AG) genotype obtained in the present study is in consonance with the findings of Terman et al (2016), who reported 1B2B genotype was the most frequent genotype with a frequency of 0.50 and the 1B1B genotype was least frequent (0.12) in wild boars. Likewise, Buske et al (2006) also found that farrowing, farrowing intervals, litter size at birth, litter size at weaning, average birth weight, average weaning weight; and body weight were recorded at monthly intervals.…”
Section: Resultssupporting
confidence: 92%
See 4 more Smart Citations
“…The genotypic frequencies of AA, AG and GG were 0.157, 0.478 and 0.365 and allelic frequencies of A and G were 0.396 and 0.604, respectively, in the studied breed. The frequency of 1B2B (AG) genotype obtained in the present study is in consonance with the findings of Terman et al (2016), who reported 1B2B genotype was the most frequent genotype with a frequency of 0.50 and the 1B1B genotype was least frequent (0.12) in wild boars. Likewise, Buske et al (2006) also found that farrowing, farrowing intervals, litter size at birth, litter size at weaning, average birth weight, average weaning weight; and body weight were recorded at monthly intervals.…”
Section: Resultssupporting
confidence: 92%
“…Thus, genetic variations could be probably affected by artificial selection, because selection may significantly change the genotypic and allelic distribution of GPX5 gene. Terman et al (2016) also found that the investigated pig populations were not in Hardy-Weinberg equilibrium, which is compatible with our findings. In this study, a total of one SNP locus in GPX5 i.e., SNP-HinfI (g.1896A>G) detected in the Intron 1, and no mutation caused a change of amino acid (Fig.…”
Section: O N L I N E C O P Ysupporting
confidence: 92%
See 3 more Smart Citations